Krüppel-like factor 5 -mediated Sirtuin6 promotes osteogenic differentiation and inhibits inflammatory injury of lipopolysaccharide-induced periodontal membrane stem cells by inhibiting nuclear factor kappa-B pathway. Issue 3 (1st March 2022) - Li, Chanxiu; Xiao, Feng; Wen, Yunsheng; Wu, Jian; Huang, Nannan
ABSTRACT: Periodontitis is a chronic infectious disease that causes inflammation and immune response and has an ultimate impact on the health of the whole body. Sirtuin6 (SIRT6) and Krüppel-like factor 5 (KLF5) have been reported to regulate the inflammatory response and play an important role in the development of periodontitis. LPS was adopted to induce periodontal ligament stem cells (PDLSCs) to construct a periodontitis cell model. SIRT6 expression was assayed through RT-qPCR and Western blot. Subsequently, after SIRT6 was overexpressed, CCK8 was to appraise cell viability. ELISA analysis was used to estimate inflammatory response. ALP staining, ARS staining, and Western blot were used to detect osteogenic differentiation. The JASPAR website then predicts the binding of transcription factor KLF5 to SIRT6 promoter. The interaction between KLF5 and SIRT6 was verified by a luciferase reporter and ChIP assays. Additionally, the osteogenic differentiation and inflammation in LPS-induced PDLSCs transfected with Ov-SIRT6 and si-KIF5 were also explored. Finally, the protein levels of the nuclear factor kappa-B (NF-κB) pathway-related factors were detected by Western blot to further explore the mechanism. There was a marked decrease in SIRT6 expression in LPS-induced PDLSCs. SITR6 overexpression prevented LPS-induced cell viability loss and inflammation, while promoting osteogenic differentiation. In addition, KLF5 could transcriptionally activate SIRT6. Further, KLF5 knockdown reversed the impacts of SIRT6 on the proliferation, inflammation, and osteogenic differentiation of LPS-induced PDLSCs via mediating NF-κB pathway. Overall, KLF5-mediated SIRT6 promoted the viability and osteogenic differentiation, while inhibiting the inflammatory response of LPS-induced PDLSCs by inhibiting NF-κB pathway. GRAPHICAL ABSTRACT: uf0001